The appearance of truth – the truth of appearance. Steen Steensen Blicher: Præsten i Vejlby - Gergye, László (Folia Scandinavica Posnaniensia, 2019)
The paper discusses a piece by one of the most outstanding Danish short story writers of the 19th century, structured around the convential elements of detective stories. Relying on Jean Baudrillard’s simulacra theory, it attempts to demonstrate the process of how the intriguer Morten Bruus, by a successful use of make-believe, manages to incriminate a pastor, Søren Qvist, in a murder although he is innocent. Bruus’s manipulative strategy prevails in the end: he succeeds at deceiving both his environment and the judge presiding in the case, and the accused is executed. The truth is revealed only twenty years later when Niels Bruus, long thought to be dead, returns. Drawing on Derrida’s legal philosophy, the analysis seeks to expose the problematic nature of justice on earth, and it shows by revisiting certain ideas of Kierkegaard that even in the shadow of death, steadfast faith in divine justice can get us over our fears and the eternal uncertainty deriving from the essence of human existence.